From growing up in the jungle to practicing ayahuasca in the city: An exploration of the globalisation of ayahuasca in terms of authenticity, self-care, and the challenges of such globalisation for medical anthropology - Kohek, Maja; Bouso, José Carlos; Oña, Genís (Revista de Antropología Social, 2023)
This paper is a case study of a woman who migrated to Barcelona from the Brazilian rainforest seventeen years ago and her journey to becoming a healer working with ayahuasca, kambô (frog venom), and sananga (herbal eye drops). The concepts of authenticity, communitas, and self-care are discussed. We argue that shamanism, religion, and healthcare are all fluid, dynamic processes that influence, interact with, and absorb their surroundings. Exploring the compatibilities between beliefs and practices from different traditions mixed with biomedical approaches helps us broaden our understanding of the relationships between religion or spirituality, health, and well-being. We conclude this manuscript by requesting the medical anthropology community offer insight into the complex challenges arising with the globalisation of ayahuasca practices.